The role of vascularized flaps in the treatment of proximal pole avascular necrosis in scaphoid non-unions - Guzzini, Matteo; Lanzetti, Riccardo Maria; Proietti, Lorenzo; Lupariello, Domenico; Iorio, Raffaele; Ferretti, Andrea (Acta Biomedica Atenei Parmensis, 2019)
Objectives: The purpose of this study is to evaluate the clinical and radiological outcomes of scaphoid non unions surgically treated with bone graft versus medial condyle corticoperiosteal free flaps. Materials and Methods: 32 patients were divided in 2 groups. Group A (17 patients 12male, 5 females, mean age 35 years old) treated with bone grafts; Group B (15patients 11 male, 4 females, mean age 33 years old) treated with medial condyle cortico periosteal free flap. A radiological follow up was performed about every 30 days after surgery until the complete healing and at 12-month follow-up. The clinical follow up was performed at 6 and 12 months from surgery. Functional assessment was provided by Mayo wrist score and Visual Analogic Scale (VAS). Results: The average length of follow up was 12.52 months ± 1.36. In group A 60% of patients healed in 4.4 ± 1months with a reduction of 28.4% of healing times in group B (p